DEVELOPING BUSINESS ENVIRONMENTS AND FINANCIAL STRATEGIES FOR MANAGING COUNTRYSIDE WALKING TOURISM (CWT) - Danka Milojković; Vule Mizdraković; Milena Nikolić (Ekonomika Poljoprivrede (1979))
Legal framework, infrastructure expansion, community engagement, capacity development, public-private partnership (PPP), cluster development, and financial strategies are variables that contribute to creating a business environment  for CWT development. This research aims to analyse aspects of managing the abovementioned variables for a sustainable and pleasant experience for residents and visitors. The data collected through the survey were analysed using non parametric statistical methods. The analysis showed that regulation and infrastructure (64.2%) are prerequisites for encouraging CWT development, and education of the local population about clustering contributes to this. PPP projects mean greater attractiveness of rural tourist destinations (80.1%). Financial strategies for the development of CWT are donations, vouchers, and joint ventures. Adolescents, students, and families with children prefer the crowdfunding strategy. The authors propose strategic planning, management, and monitoring of key business environment variables for CWT development. Further research should focus on safety, security, accessibility, environmental sustainability, technology integration, and visitor feedback.